Sự trỗi dậy của Trung Quốc trong nền kinh tế toàn cầu và hệ quả đến các quốc gia ASEAN-6 - Huỳnh Thái, Huy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
The structure of the world economy has profoundly changed over the past three decades because of the globalization and China’s rise. The substantial changes in trade linkages between China, the U.S. and ASEAN-6 have influenced a mechanism of international business cycle transmission to ASEAN-6. In order to investigate the effect, the paper employs a Global Vector Autoregressive (GVAR) model with three different sets of trade weights to account for the alterations in international trade linkages. The results show that the long-term impact of a China GDP shock on ASEAN-6 economies (except for Thailand) is much stronger in 2016 than in 2000. Additionally, a GDP shock in the U.S. mostly has a lower impact on GDP ASEAN-6 (except for Indonesia) in 2008 than in 2000. Also, these findings reveal the reasons why the ASEAN economies can quickly recover from the 2008 global crisis